Integrated thematic direction: sustainable development – management models – organizations – policies - Board, Editorial (Leadership, Society, Strategic Visions, 2021)
Main highlights in the discussion. Sustainability is analyzed as a dynamic concept, updated with new visions, policies, goals and tools. An innovation accelerator management model is justifi ed, leading to increased business growth and a quality â€œmethodology of working within the organizationâ€.